Database Programming with CSharp - Thomsen, Carsten (Apress, 2012)
This book is targeted at intermediate users, meaning users who already know a little about Visual Studio .NET and perhaps previous versions of Visual Basic. Basic knowledge of Object Oriented Programming (OOP), ADO, and database design is also assumed. Parts of the book are at a beginner level and other parts are at a more advanced level. The beginner-level material appears where I feel it is appropriate to make sure you really understand what is being explained. The many listings and tables make this a good reference book, but it's also a book intended for reading cover to cover. It will take you through all the data access aspects of Visual Studio .NET with example code in C#. This includes how to create the various database items, such as databases, tables, constraints, database projects, stored procedures, views, triggers and so on. For the most part, I show you how to do this from within the VS .NET IDE as well as programmatically where possible. You'll build on the same example code from the beginning of the book until you wrap it up in the very last chapter. The example application, UserMan, is a complete user management system that includes SQL Server, Active Directory, and Message Queuing.x